Desain Kamus Saku Imla’ untuk Pembelajaran Mahārah Kitābah - Anilla F. Hermanda (Lisanan Arabiya: Jurnal Pendidikan Bahasa Arab, 2020)
This article describes writing (maharah kitabah) is one of many problems of Arabic learning which stay every day and must finish it, not only for the student but also for university students. That's all because many students don’t know what the main concept of Arabic language especially in writing Arabic, so a lot of students make some basic mistake in the writing of Arabic. Besides that, the main concept of the Arabic language, especially qawaid imla’ hasn’t owned by the student. Based on that problem the purpose of this research because a researcher wants to develop about imla’ dictionary to helping the student to an understanding of Arabic language writing’s rule. This research is a result of research in MAN 1 Pamekasan which uses a preliminary research method with 4D’s model which uses two stages, define and design. The result of this research is a design of imla’ pocket dictionary with a practical formula based on hijaiyah word classification. This a dictionary made as support of writing’s learning skill for senior high school.